Switching Algorithm for Leakage Current Reduction in a PV- No Transformer Inverter System - M. N. H. Khan; M. R. Hasan; M. K. Alam (Institute of Advanced Engineering and Science, 2016)
Electricity generation purposes renewable energy brings a important role especially Photovoltaic (PV) panels that can be covered our basic energy (electricity) needs. This photovoltaic panels cover a domestic level (solar power for home), commercially (solar power for commercial applications) or at the community level. Here used this photovoltaic panel as an input of PV-transformer-less inverter topology which has been compared with existed H6 transformer-less inverter topology. It’s possible to reduce the leakage current with inclined the output voltage that has been shown here by using proposed topology. This topology is made by using two extra switches with filter. Moreover, overall system actually verified with Pulse Width Modulation (PWM) switching technique.